Health-related quality of life assessment among patients with inflammatory bowel diseases after surgery – review - Grażyna Bączyk; Dorota Formanowicz; Łukasz Gmerek; Piotr Krokowicz (Gastroenterology Review)
Aim of the work was to review systematically the published literature addressing whether quality of life (QoL) and health-related QoL (HRQoL) are influenced by surgery among patients with inflammatory bowel disease (IBD). Electronic databases and published articles were searched to identify relevant studies published in the years 1990–2015. Then, a multistep selection was undertaken to identify articles that met specific selection criteria, such us specific key-words (IBD, HRQoL, ulcerative colitis (UC), Crohn’s disease (CD), and surgery), and the population was assessed (studies concerning patients < 18 years old were excluded). The review included 27 studies that were evaluated in the context of the influence of surgery on QoL and HRQoL. Concluding, with the increase in the incidence of IBD, monitoring of QoL is an important indicator of the health effects at each stage of the surgical treatment.